Endovascular repair of thoracoabdominal aneurysms: results of the first 48 cases - Ferreira, Marcelo; Lanziotti, Luiz; Cunha, Rodrigo; d’Utra, Guilherme (Annals of Cardiothoracic Surgery; Vol 1, No 3 (September 26, 2012): Thoracoabdominal Aortic Aneurysm Repair, 2012)
Background: In 2006, we began our experience with a novel technology for fully endovascular thoracoabdominal aneurysm repair, based on a custom-made, branched stent graft design. After 48 cases, we have learned and achieved substantial progress both in technical and in clinical skills. This paper describes the partial results of this ongoing experience. Methods: Patients in this series were selected for the presence of thoracoabdominal aortic aneurysms, with or without dissection, which was present in one patient. The observation of extensive anatomical variations in several patients prompted changes in many of the basic stent graft configurations, which are also described. Results: Between August 2006 and June 2012, 48 patients were treated consecutively with custom-made branch stent grafts. The five patients with the longest follow-up available so far are at 71, 65, 60, 54 and 51 months post-procedure. The operative mortality rate, defined as death during or within 1 month of surgical hospitalization, was 21% (10 patients); each case is described herein. During postoperative follow up, 9 patients died from causes not directly related to aneurysmal disease, at 3, 18, 20, 22, 24, 24, 37, 44 and 46 months. The main causes of death were myocardial infarction (4 cases), cancer (2 cases), gastrointestinal hemorrhage (1 case), ischemic stroke (1 case), and sepsis (1 case). Permanent paraplegia occurred in one patient (2.08%). Conclusions: It is still too soon to compare the results of endovascular repair of thoracoabdominal aneurysms with those of open surgical series. Despite the active and rapid progress currently observed for the endovascular method, it is still far from reaching its state-of-the-art plateau or becoming a gold standard. Further technological and technical advances in endovascular stent grafting seem to have a clear potential to provide very satisfactory operative outcomes for thoracoabdominal aortic aneurysms.